Augmented reality sandboxes: children's play and storytelling with mirror worlds. Issue 1 (2nd January 2021) - Leinonen, Teemu; Brinck, Jaana; Vartiainen, Henriikka; Sawhney, Nitin
ABSTRACT: Augmented Reality (AR) technology has provided a new technological platform for 'mirror worlds', where layers of information, meaning, and functions are integrated with a digital twin of the real world. To explore mirror worlds, we designed and developed +Andscape, an interactive AR sandbox. In this conceptual and empirical case study, we observed children's (5–6-year-old, N  = 16) collaborative play and storytelling with +Andscape. The qualitative content analysis from observational video-based data allows us to infer how children's play with the AR sandbox engaged their questioning and reflections of both the real world events and the computational mirror worlds. The use of the tool triggered children's imagination and opened for them a story world for exploration of current media events in a unique way. We conclude that when introducing mirror worlds, the focus should be on creative play, participation and storytelling through which the children can construct their own story worlds.